Effects of plyometric jump training on measures of physical fitness and lower-limb asymmetries in prepubertal male soccer players: a randomized controlled trial - Sammoud, S.; Negra, Y.; Bouguezzi, R.; Ramirez-Campillo, R.; Moran, J.; Bishop, C.; Chaabene, H. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background High level of physical fitness is a paramount soccer performance factor. As such, developing key components of physical fitness such as sprinting, jumping, and change of direction (CoD) at an early age empowers both short- and long-term performance success. Although previous research in prepubertal male soccer players has reported physical fitness performance enhancements following plyometric jump training (PJT), the effects on inter-limb asymmetries remain unclear.